Evaluación de los niveles de empatía médica en médicos residentes de un hospital general en Perú - Huarcaya-Victoria, Jeff (2019)
Abstract: Objective To evaluate the level of empathy in medical residents in the Hospital Nacional Guillermo Almenara Irigoyen (HNGAI), as well as its relationship with the religious attitude and other personal and sociodemographic variables. Material and methods Observational and cross-sectional study using a questionnaire conducted on the HNGAI, Lima, Peru. The Jefferson Medical Empathy Scale (EEMJ), the Religious Attitude Scale (EAR), and a sociodemographic data collection card were used to collect data from medical residents who entered the HNGAI medical residency program during the years 2016 and 2017. Results The mean score of empathy levels was 118.74. Non-significant differences were found in the levels of empathy related to the choice of specialty (‘people-oriented’: 119.58 versus ‘technology-oriented’: 117.15, P = .189); and gender (women: 119.5 versus males: 118.05, P = .408). Significant differences were found in the levels of empathy related to having had a professional model in treating the patient (P = .004) and referring to belonging to a religion (Catholic/Protestant/Evangelical) (P = .003). A direct correlation was found between the EEMJ and the EAR (r = .249, P = .006). Conclusions The residents who identify themselves as belonging to a religion obtained higher levels of empathy, along with those who mention having a professional model in the treatment of the patient. Prospective studies should be conducted in order to evaluate the evolution of medical empathy in medical residents. Determining the factors that would intervene in their erosion would also be useful.